Later-life depressive symptoms and anxiety attacks in displaced and nondisplaced populations - Christine Ulke (Journal of Affective Disorders Reports, 2021)
Background: Forced displacement has been suggested as a potential cause for depression and anxiety in later life. Little research has been done on the influence of the host country's socio-political system. Here we examine whether the later-life effects of displacement on mental health (i.e. depressive symptoms and anxiety attacks) differ between socio-political contexts. We hypothesized that between-group differences (displaced vs. nondisplaced) in self-rated depression scores and frequencies of anxiety attacks are more pronounced in East versus West German populations. Methods: Datasets from three representative nationwide surveys (2002, 2003, 2007) were analyzed; study participants born 1946 and earlier were included. The final sample comprised 2239 participants, including 1235 women. The depression and anxiety modules of the Patient Health Questionnaire (PHQ-D) were used to assess current anxiety and depression. Results: Of the total sample, 15.4% reported WW2 displacement, 18.9% (n = 129) in the East and 13.9% (n = 216) in the West German sample. Concerning depression, we found significant between-group differences (displaced vs. nondisplaced) in the East (but not West) German sample. Concerning anxiety, both displaced East and West Germans reported a significantly higher frequency of anxiety attacks, as compared to nondisplaced individuals. Differences between effect sizes (East vs. West) were significant for depression, and anxiety after controlling for age and sex. Limitations: Limitations include the self-rated assessment, not controlling for the confounding impact of the German reunification, and the cross-sectional study design. Conclusion: Results corroborate the assumption of an unsupportive socio-political context as a potential predisposing factor for later-life anxiety or depression after forced displacement.